Parametric modeling and FPGA based real time active vibration control of a piezoelectric laminate cantilever beam at resonance. (October 2015) - Parameswaran, Arun P; Gangadharan, KV
The operational efficiency and life of mechanical systems/structures depends to a large extent on their vibration control. Continuously occurring vibrations on the systems can cause fatigue and the effects of these vibrations are particularly severe if they occur at a frequency matching with that of the concerned system's natural frequency – a stage called resonance. This paper focuses on achieving active vibration control of a smart cantilever beam at its first resonant frequency as it is at this stage that maximum damage to the system performance is expected. The smart system is modelled in the parametric domain using finite element modeling techniques and the obtained model is validated through experimental means. The active vibration control is achieved by employing two control algorithms namely – output feedback and error based control through general purpose operating system (LabVIEW on Windows 7) as well as in real time operating system (LabVIEW FPGA coupled with compact reconfigurable input output modules) and the performances are compared thereby justifying the importance of the deterministic and reliable real time control over the usual PC based control in experimental studies.